Reproductive and Sexual Health of People with Physical Disabilities: A Metasynthesis - Nguyen, Thi Tu An; Liamputtong, Pranee; Monfries, Melissa (Sexuality and Disability : A Journal Devoted to the Psychological and Medical Aspects of Sexuality in Rehabilitation and Community Settings, 2016)
This article provides an overview on reproductive and sexual health of people with physical disabilities in developed and underdeveloped countries from 1995 to 2011. Based on the metasynthesis approach, the authors reviewed 15 qualitative studies. These studies were searched using Medline, CINAHL, CINAHL (health), ProQuest Central, Google Scholar, Cochrane, Embase, Informit Health, Sciences Direct, Pubmed, Pubmed Health, AAHD (abstracts), ProQuest Journal (sexuality and disability) and were also manually searched. All studies were judged on their qualities using the Critical Appraisal Skills Programme. Reproductive health, sexual attractiveness and experiences, reproductive and sexual health knowledge, and dealing with reproductive and sexual health issues were four main themes that emerged from these studies. This paper proposes a new model to explain the factors that impacted the reproductive and sexual life of people with physical disabilities: internal and external factors. Implications for health and social care are discussed in light of the findings.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; capacitisme; care; cours; discipline; justice reproductive; médecine; métasynthèse; premier cycle; psychologie; périodes historiques; ressource en ligne; santé; sciences; sciences humaines; sex1920; sexualité; systèmes d'oppressions; thématiques; travail social

Sur le terrain de l’émotion : déconstruire la question émotionnelle en géographie pour reconstruire son horizon épistémologique - Volvey, Anne (Carnets de géographes, 2016)
Ce texte interroge la part esthétique de la création géographique et présente des corpus et des outils théoriques et conceptuels pour travailler cette question d’épistémologie disciplinaire. Dans une première partie, il s’attache à une généalogie de l’évolution de la prise en compte du phénomène de l’émotion dans la recherche – de problème en fait significatif, puis en moyen de la connaissance géographique – à travers les réflexions conduites, notamment par la géographie féministe et qualitative anglophone, sur la méthodologie disciplinaire du terrain. Sur ce fondement, il présente les trois régimes esthétiques de savoir spatial attachés aux standards méthodologiques successivement adoptés par la discipline – régimes scopique du terrain masculiniste, linguistique et haptique du terrain féministe et qualitatif. Dans une seconde partie critique, en revenant sur le modèle du care privilégié par les géographies féministes et qualitatives pour reconstruire la politique de la méthode sur des bases relationnelles (ou intersubjectives), il traite des limites politiques rencontrées par ces géographies pour fonder pleinement un autre régime de scientificité disciplinaire à partir de l’émotion. A contrario, il montre comment la psychanalyse du care (ou psychanalyse transitionnelle) prise au sérieux, non seulement pour ses trouvailles méthodologiques et conceptuelles mais pour sa théorie relationnelle de l’identité-subjective, peut devenir l’outil d’élaboration d’une épistémologie qualitative basée sur l’émotion.
https://journals-openedition-org.proxy.bibliotheques.uqam.ca/cdg/541
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; care; corps; discipline; géographie; psychanalyse; périodes historiques; ressource en ligne; sciences; sciences humaines; thématiques; émotions; épistémologie; étude qualitative

Race, gender, class, sexuality (RGCS) and hypertension - Veenstra, Gerry (Social Science & Medicine, 2013)
Informed by intersectionality theory, a tradition that theorizes intersecting power relations of racism, patriarchy, classism and heterosexism, this paper investigates the degree to which race, gender, class and sexuality manifest distinct and interconnected associations with self-reported hypertension in nationally-representative survey data from Canada. Binary logistic regression is used to model the main effects of, and interactions between, race, gender, education, household income and sexual orientation on hypertension, controlling for age, using data from the 2003 Canadian Community Health Survey (n = 90,310). From a main effects (‘additive’) perspective, Black respondents, respondents with less than high school and poorer respondents were significantly more likely than White respondents, university-educated Canadians and wealthier Canadians, respectively, to report hypertension. However, the interactive models indicate that the additive models were poor predictors of hypertension for wealthy Black men, wealthy South Asian women, women with less than a high school diploma and wealthy bisexual respondents, who were more likely than expected to report hypertension, and for poor Black men, poor South Asian women, poor South Asian men and women with a university degree, who were less likely than expected to report hypertension. It appears that, with regard to blood pressure at least, Canadians experience the health effects of education differently by their genders and the health effects of income differently by their identities defined at the intersection of race and gender. This study provides empirical support for the intersectional approach to cardiovascular health inequalities by demonstrating that race, gender, class and sexuality cannot be disentangled from one another as predictors of hypertension.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; capitalisme; discipline; hétérosexisme; intersectionnalité; médecine; patriarcat; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; santé cardiovasculaire; sciences; sexisme; systèmes d'oppressions; thématiques